Structural changes during the gelation of poly(vinyl chloride) plastisols - Makarewicz, E.; Shyychuk, I.; Mroczyńska, K. (Polimery, 2021)
The study on thermal stability of polyvinyl chloride (PVC) plastisols gelled at temperatures 140 and 160 °C was carried out. Four different PVCs were used: PVC E-68 (Poland), Pevikon P-682 (Sweden), Slovinyl EP-702 (Slovakia) and Vestolit B-7021 Ultra (Germany). Four plasticizers were applied: di-2-ethylhexyl phthalate (DOP), 1,2-cyclohexanedicarboxylic acid diisononyl ester (Hexamoll DINCH), dipropylene glycol dibenzoate (S-9100) and dioctyl adipate (DOA). The morphology and size distribution of polymer particles were studied with confocal microscopy. ATR-FTIR spectra of the gelled plastisols were recorded, indicating the formation of multiple bonds, ester and ether bond as well as oxygen-containing groups. Thermal stability of the plastisols was evaluated by means of thermogravimetry in air atmosphere. The effects of degradation processes occurring during the gelation of plastisols on the temperatures of initial and final decomposition as well as maximum rate of PVC decomposition were assessed. It was found that the changes in the gelled plastisol membranes depend essentially on the poly(vinyl chloride) type and to alesser extent on the plasticizer used.